Speaking Anxiety in Chinese Language Learning Among Non-Chinese Learners in Malaysia - Ting, Hie Ling; Chong, Pei Qi; Lam, Kai Chee; FS, Sunarti (Faculty of Cultural Sciences Universitas Sebelas Maret, 2023)
Numerous studies indicate most of the foreign language learners experience certain level of anxiety and usually they experience anxiety in their speaking skills. Hence, this study examines the speaking anxiety in Chinese Language learning among non-Chinese Beginner learners from University Teknologi MARA (Sarawak). The questionnaire which was developed by Horwitz, Hor-witz and Cope (1986) was used in this study. SPSS 25.0 was used to analyze the scores. The result revealed non-Chinese beginner learners experienced speaking anxiety in Chinese language learning. Majority of them experience a moderate level of speaking anxiety in Chinese language learning. The main factor that contributed to non-Chinese beginner learners’ speaking anxiety was communication apprehension. It was followed by test anxiety and fear of nega-tive evaluation.